Karakterisasi Adsorben dari Limbah Pelepah Kelapa Sawit Teraktivasi Natrium Hidroksida untuk Adsorpsi Mangan - Sara, Titien; Mistar, Eka Marya (Talenta Publisher (Universitas Sumatera Utara), 2025)
The use of heavy metals including manganese (Mn) in various industrial applications such as mining and metal processing has triggered water pollution and caused a negative impact on human health. This study aims to evaluate the adsorbent properties activated by sodium hydroxide from oil palm frond waste for Mn(II) adsorption from the water via a fixed-bed column at flow rates of 5, 10, and 15 mL/min. The morphology analysis exhibited high pore development in the adsorbent after the activation process using sodium hydroxide. Similar to the results of functional group analysis, the activated adsorbent indicated an increase in oxygen-containing functional groups that are beneficial aspects in the adsorption process. In the continuous adsorption applications, a flow rate of 5 mL/min presented an optimum adsorption capacity of 36.58 mg/g compared to flow rates of 10 mL/min and 15 mL/min: 28.94 mg/g and 22.07 mg/g, respectively. The findings of the present work denote the utility and effectiveness of oil palm frond waste as an eco-friendly raw material for the fabrication of adsorbent with relatively favorable properties for Mn(II) adsorption.